Implikasi Faktor Pertumbuhan Rohani Keluarga Kristen Berdasarkan Efesus 5:22-6:4 Bagi Pembinaan Keluarga di Gereja - Deni Triastanti; Krido Siswanto; Enggar Objantoro (Integritas: Jurnal Teologi, 2021)
The implications of the spiritual growth factors for Christian families based on Ephesians 5: 22-6: 4 for family formation in the church. This writing uses a hermeneutic literature study to analyze the text of Ephesians 5: 22-6: 4. The author also includes a qualitative descriptive analysis, in order to describe the discussion related to the Christian family to find implications for the formation of the Christian family in the church. From the results of the research, the author's interview with 5 young family members, the wives obey the authority of the husband as the head of the family as many as 4 participants, the husband in loving his wife by providing services to the welfare of the wife both physically and spiritually there are 4 participants, the children describe the role His obedience, namely depending on the attitude of the two parents, there are 3 participants and the parents (husband and wife) carry out their role in educating children by being spiritual role models through attitudes and actions, there are 3 participants. As an implication for family formation in the church, namely, the wife in her role of submission and respect to the husband, as the husband has the role of head and loves the wife, as children have an attitude of obedience and respect to both parents and as parents (husband and wife) has the role of not arousing children's anger and educating children in God's teachings.